2019
DOI: 10.1136/bmjopen-2018-024582
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the readability and patient comprehension of rheumatology medicine information sheets: a cross-sectional Health Literacy Study

Abstract: ObjectivesPatients are often provided with medicine information sheets (MIS). However, up to 60% of patients have low health literacy. The recommended readability level for health-related information is ≤grade 8. We sought to assess the readability of MIS given to patients by rheumatologists in Australia, the UK and Canada and to examine Australian patient comprehension of these documents.DesignCross-sectional study.SettingCommunity-based regional rheumatology practice.ParticipantsRandom sample of patients att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 43 publications
2
44
0
1
Order By: Relevance
“…In addition, those with limited FHL accessed health information from fewer resources and were more likely to use television but not printed media or health organization documents as their main source of health information (Yoshida, Iwasa, Kumagai, Suzuki, & Yoshida, 2014). Oliffe et al (2019) found that in comparison to patients with adequate FHL their counterparts with limited FHL were less likely to give correct answers to questions indicating an understanding of medication labels and were more likely to make errors while demonstrating medication administration. Limited FHL was also a strong indicator of poor processing of oral communication.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, those with limited FHL accessed health information from fewer resources and were more likely to use television but not printed media or health organization documents as their main source of health information (Yoshida, Iwasa, Kumagai, Suzuki, & Yoshida, 2014). Oliffe et al (2019) found that in comparison to patients with adequate FHL their counterparts with limited FHL were less likely to give correct answers to questions indicating an understanding of medication labels and were more likely to make errors while demonstrating medication administration. Limited FHL was also a strong indicator of poor processing of oral communication.…”
Section: Discussionmentioning
confidence: 99%
“…Using previously described methodology, multiple readability formulae were used to improve the reliability of measures, with scores averaged to form a composite readability score for individual websites (18,(21)(22)(23)(24)(25)(26)(27)(28). A cutoff of an 8th-grade or lower reading level (#8.9 grade level) was chosen to define readability.…”
Section: Readabilitymentioning
confidence: 99%
“… 22 Another distinctive advantage is the ability of these to communicate important information across people of varied subject matter related to literacy, making them particularly useful for public health advisories. 23 24 25 26 They are also being used to improve research literacy among trial participants. 27 …”
Section: Introductionmentioning
confidence: 99%